Clinical and haemodynamic effects of percutaneous edge-to-edge mitral valve repair in atrial versus ventricular functional mitral regurgitation. (14th October 2021) - Claeys, M J; Debonnaire, P; Bracke, V; Bilotta, G; Shkarpa, N; Vanderheyden, M; Coussement, P; Vanderheyden, J; Van De Heyning, C; Cosyns, B; Pouleur, A C; Lancellotti, P; et al.
Abstract: Background: Atrial functional mitral regurgitation (A-FMR) is a novel entity characterized by a MR due to atrial remodeling but with preserved left ventricular (LV) systolic function. Purpose: To assess the clinical and haemodynamic impact of percutaneous edge-to-edge mitral valve repair with MitraClip in patients with A-FMR as compared to ventricular (V)-FMR. Methods: MR grade, functional status (NYHA class), and major adverse cardiac events (MACE= all-cause mortality or hospitalization for heart failure (HF)) were evaluated in 52 A-FMR patients (pts.) and in 307 V-FMR pts. who underwent MitraClip implantation in 7 Belgian centers. In a subgroup of 56 pts (10 A-FMR and 46 V-FMR) haemodynamic assessment during a symptom-limited exercise echocardiography was performed before and 6-month after intervention. Results: MitraClip implantation resulted in similar MR reductions in A-FMR and V-FMR (MR grade ≤2 at 6-month in 94% versus 82%, respectively (p=0.08)) and was associated with improvement of functional status in both groups (NYHA class ≤2 at 6 months in 90% versus 80%, respectively (p=0.2)). Serial haemodynamic assessment revealed that the cardiac output at 6-month was significantly higher in A-FMR pts. both at rest (5.1±1.5 L/min versus 3.8±1.5 L/min, p=0.002) and during peak exercise (7.9±2.4 L/min versus 6.1±2.1 L/min, p=0.02). Also the reduction in systolic pulmonary artery pressure (sPAP) was more pronounced in A-FMR: Δ sPAP at rest – 13.1±15.1 mmHg versus – 2.2±13.3 mmHg (p=0.03). During a follow-up period of 1.3±1.2 years MACE rate was significantly lower in A-FMR versus V-FMR with an adjusted OR of 0.46 (95% CI 0.24–0.88, see figure), which was mainly driven by a reduction in HF hospitalization. Conclusion: Percutaneous edge-to-edge mitral valve repair with MitraClip is at least as effective in A-FMR as in V-FMR in reducing MR. But, the haemodynamic and clinical impact is stronger in A-FMR pts. Funding Acknowledgement: Type of funding sources: None.